The Experience Maker How to Create Remarkable Experiences That Your Customers Can?t Wait to Share - Dan Gingiss (New York Morgan James Publishing, 2022)
Competition is tougher than ever these days, and competing on price or product just doesn?t work as well anymore. So how can companies stand out in a crowded marketplace that is constantly evolving?
Keywords: Consumer behavior